2008
DOI: 10.1002/ijc.23577
|View full text |Cite
|
Sign up to set email alerts
|

Single‐nucleotide polymorphism‐mass array reveals commonly deleted regions at 3p22 and 3p14.2 associate with poor clinical outcome in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common solid tumors in the world with poor prognosis. Deletion of chromosome 3p is one of the most frequent chromosomal alterations in ESCC, suggesting the existence of one or more tumor suppressor genes (TSGs) at this region. In the present study, a recently developed high-throughput and high-resolution technology, single-nucleotide polymorphism (SNP)-mass array, was applied to investigate loss of heterozygosity on 3p in 100 primary ESCC cases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…CHL1 is a member of the family of L1 neural cell adhesion molecules and has been reported to have regulatory functions that are pivotal to nervous system development (41). Additionally, a low-level transcript of CHL1 associated with loss of 3p26.3 has been reported in esophageal squamous cell carcinoma (42). These observations in combination with our results suggest that CHL1 is a candidate tumor suppressor gene associated with aggressiveness of OSCC.…”
Section: Discussionsupporting
confidence: 83%
“…CHL1 is a member of the family of L1 neural cell adhesion molecules and has been reported to have regulatory functions that are pivotal to nervous system development (41). Additionally, a low-level transcript of CHL1 associated with loss of 3p26.3 has been reported in esophageal squamous cell carcinoma (42). These observations in combination with our results suggest that CHL1 is a candidate tumor suppressor gene associated with aggressiveness of OSCC.…”
Section: Discussionsupporting
confidence: 83%
“…The genetic abnormalities of these genes at 3p have an important role in the development of lung cancer and renal cancer. In our recent study, we provided the first evidence that 3p24 was one of the most frequently deleted regions in ESCC and PCAF was identified as a candidate TSG (Qin et al, 2008). In this study, we found that mRNA expression of PCAF was absent in 44.4% of ESCC cell lines and 57.5% of primary ESCC tumors.…”
Section: Discussionmentioning
confidence: 54%
“…When KYSE510 cells were treated with 5-aza-dC, the expression of PCAF could be reactivated (Figure 2d), indicating that both promoter methylation and DNA copy loss contributed to the absent expression of PCAF gene. In our previous study, the loss of one PCAF allele has been detected in 14/40 (35%) of ESCC specimens by single-nucleotide polymorphism array (Qin et al, 2008). In these cases, the downregulation of PCAF was detected in 23 (57.5%) of the specimens.…”
Section: Downregulation Of Pcaf Is Frequently Detected In Esccsmentioning
confidence: 79%
See 1 more Smart Citation
“…In acute myeloid leukemia (AML), patients with high expression of miR-191 have significantly worse overall and event-free survival than AML patients with low expression (20). Furthermore, PLCD1 and RNF139, two predicted candidate target genes of miR-191, are tumor suppressors in esophageal squamous cell carcinoma and human hereditary kidney cancer, respectively (21,22). miR-93 is up-regulated in gastric cancer tissues compared to the corresponding normal tissues (23).…”
Section: Discussionmentioning
confidence: 99%